2012
DOI: 10.1007/s10695-012-9626-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin genes in fish: differential expression on exposure to estradiol

Abstract: Three types of vitellogenins (Vgs) namely vitellogenin A (VgA), vitellogenin B (VgB) and vitellogenin C (VgC) have been identified in fishes. The existence of VgA and VgB is reported in the Indian freshwater murrel Channa punctatus. Gene-specific primers were designed using available nucleotide sequences in National Centre for Biotechnology Information (NCBI), for amplification of VgA and VgB cDNA. Differential processing of Vgs is evident in many fishes. Adult male murrel expressed both the VgA and VgB genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In order to investigate whether miRNAs play some roles in testis development, we checked the expression of miR-200 family members in testis treated with high dose of estrogen that would impair testis development and cell proliferation [33]. Expression of five miR-200 family members (200a-3p, 200b-3p, 200c-3p, 141-3p, 429b-3p) was significantly up-regulated at 12 h, and were gradually rising to a higher value at 96 h after EE2 treatment compared to the expression of control group (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate whether miRNAs play some roles in testis development, we checked the expression of miR-200 family members in testis treated with high dose of estrogen that would impair testis development and cell proliferation [33]. Expression of five miR-200 family members (200a-3p, 200b-3p, 200c-3p, 141-3p, 429b-3p) was significantly up-regulated at 12 h, and were gradually rising to a higher value at 96 h after EE2 treatment compared to the expression of control group (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous estrogen treatment studies, the dose of EE2 (10 ug/g body weight) was considered as a relative high concentration [33], [52], [53]. Under high dose of EE2 treatment, testis development and spermatogenesis is impaired, including inhibition of spermatogonia proliferation and differentiation, apoptosis of undifferentiated spermatogonia and reduction of seminal fluid volume [31], [54][56].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the injection of adult male Indian freshwater murrel fish (Channa punctatus) with E2 (1, 10 and 40 μg/100g/body wt.) showed a dose-dependent response with respect to VTG genes expression (22). Similarly, Arukwe et al (26) observed a significant increase in VTG gene expression in a dose and time dependent pattern in rainbow trout fish (Oncorhynchus mykiss) when treated with varying doses of nonylphenol.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, we developed a real time PCR assay for VTG gene expression in A. latus. It has been demonstrated that E2, as a natural estrogen, can induce the expression of hepatic VTG gene in various fish (9,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In teleosts, the three YPs derived from Vtg (lipovitellin, Lv; phosvitin; and β′-component) play essential roles in embryonic and larval fish nutrition (Hiramatsu, Matsubara, Weber, Sullivan, & Hara, 2002). The most evolved groups of fish (Paracanthopterygii and Acanthopterygii) possess three Vtg orthologues, namely: Vtg type A (VtgA or VtgAa), Vtg type B (VtgB or VtgAb) and Vtg type C (VtgC) (Rawat, Rani, Phartyal, & Sehgal, 2013).…”
Section: Introductionmentioning
confidence: 99%